Ionic electroactive polymer actuated prosthetic finger design [Iyonik elektro-aktif polimer eyleyicili protez parmak tasarimi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
The proposed work covers an ionic electroactive polymer actuator production for use in a prosthetic finger design. The best mechanical design will be possible if it considers anatomical features of the real finger/hand structure. A number of different finger movements for different purposes are formed by the antagonistic pairs of muscles. Ionic electroactive polymer actuators are intended to be used instead of intrinsic muscles, which enable precise movement of the hand beyond the force required for movement due to their low power consumption, low noise, high power/mass ratio. © 2017 IEEE.